Baseline NT-proBNP and responsiveness to autonomic regulation therapy in patients with heart failure and reduced ejection fraction. (August 2020) - Anand, Inder; Ardell, Jeffrey L.; Gregory, Doug; Libbus, Imad; DiCarlo, Lorenzo; Premchand, Rajendra K.; Sharma, Kamal; Mittal, Sanjay; Monteiro, Rufino
Abstract: Background: Recent heart failure studies have associated lower baseline natriuretic peptide levels with improved morbidity/mortality outcomes during pharmaceutical treatment, and better clinical outcomes during neuromodulation (NM) with carotid nerve plexus stimulation for HFrEF when NT-proBNP < 1600 pg/ml. Whether baseline NT-proBNP is associated with HFrEF responsiveness to NM using vagus nerve stimulation (VNS) has not been examined. Hence, we evaluated the interaction of baseline NT-proBNP with changes in symptoms and function that occurred during chronic VNS in the ANTHEM-HF study. Methods: A repeated measures, generalized-estimating, equations model evaluated the relationship of baseline NT-proBNP values above and below 1600 pg/ml to symptomatic and functional responses in ANTHEM-HF. Results: Median (interquartile range; maximum) NT-proBNP was 868 (322, 1875; 14, 656) pg/ml (N = 58). Heart rate (HR), HR variability (SDNN), 6-minute walk distance, MLWHF mean score, and NYHA improved significantly, independent of baseline NT-proBNP. While there was a statistical interaction between baseline NT-proBNP and better LVEF improvement during VNS, LVEF improved overall in the study cohort (N = 60; 32 ± 7 to 37 ± 10%; p = 0.0042), and in those patients whose baseline NT-proBNP was below the median baseline NT-proBNP value (n = 29; 36 ± 6 to 42 ± 10%; p < 0.0025)] or above this value (n = 29; 29 ± 7 to 32 ± 9%; p < 0.05). Conclusions: In ANTHEM-HF, overall symptomatic and functional improvement during chronic VNS was independent of baseline NTproBNP. These are preliminary and hypothesis-generating findings, and the reason for a differing interaction between baseline NT-proBNP and response to CNPS and VNS remains unclear. It is anticipated that the ongoing ANTHEM-HFrEF Pivotal Study of VNS will provide additional insight.